Theory of arterial acceleration: implications for transcranial Doppler monitoring in patients with severe traumatic brain injury - Schaafsma, Arjen (Frontiers in Physiology, 2025)
The theory of arterial acceleration (AA) proposes that heart contraction is supported by a temporary and short-lasting contraction in arterial smooth muscle layers. Theoretically, it relies upon a stretch induced depolarization of smooth muscle cells at the aortic notch that spreads along the branches of the arterial tree via intercellular gap junctions. This wave of depolarization leads to a short-lasting contraction in the circularly arranged smooth muscle cells and generates a peristaltic wave from proximal to distal. In blood velocity or blood pressure recordings AA underlies the Sys1 component that becomes stronger the further it travels downstream. It adds to the Sys2 component, which is the pressure wave generated by the ejection of blood volume into the aorta that pushes forward the volume already present. This Sys2 component will follow the way of least resistance. The Sys1 component has a better tissue penetration than Sys2 and/or diastole which explains why intracranial pressure (ICP) elevation is accompanied by an increase in pulsatility index (PI). According to the author, the theory of AA leads to a better understanding of wave form morphology and, thereby, provides new perspectives for research into the detection, monitoring and treatment of ICP elevation.